Subjective health status of multimorbidity: verifying the mediating effects of medical and assistive devices - Munjae Lee; Kichan Yoon; Kyu-Sung Lee (BMC, 2018)
Abstract Background This study aimed to verify the mediating effect of using assistive devices as a factor that alleviates the relationship between multimorbidity and subjective health status. Methods This study used three-year data (2011-2013) from the Korea Health Panel (KHP). The data were jointly collected by the consortium of the National Health Insurance Service and Korea Institute for Health and Social Affairs. Results The mediating effect of using assistive devices was verified, but the direction of the effect was deteriorated subjective health. In other words, in terms of the impact of multimorbidity on subjective health, using assistive devices had a negative impact (−) on subjective health. Conclusions The current assessment system for medical devices, narrow scope for choice of assistive devices, and limited scope of health insurance benefits must change to ultimately lead to a positive mediating effect on using medical devices and on subjective health satisfaction of patients with chronic diseases. A system that embraces all ages and generations must be developed. To this end, it is necessary to expand the scope of medical devices and insurance payment in long-term care insurance for elderly users, as well as the active meaning of medical devices in terms of health insurance.